Endonasal Arteriovenous Fistula Following Transsphenoidal Resection of Pituitary Adenoma Treated with N-Butyl-2-Cyanoacrylate - Giancarlo Saal-Zapata; Walter Durand Castro; Rodolfo Rodriguez Varela (Indian Journal of Neurosurgery)
Vascular lesions of the external carotid artery after transsphenoidal pituitary surgery are rare. Immediate diagnosis must be done and endovascular embolization is the treatment of choice. We report the case of a 53-year-old woman with visual complaints who underwent transsphenoidal surgery of a pituitary adenoma with good clinical and radiological evolution. Five days after surgery nasal tampons were removed and suddenly the patient started to bleed: nasal packing and air way protection were required. Digital subtraction angiography revealed an endonasal arteriovenous fistula with a feeder from the sphenopalatine artery and drainage to sphenopalatine veins. Embolization with N-butyl-2-cyanoacrylate was performed with total obliteration of the arteriovenous fistula. We suggest that endovascular treatment of external carotid artery lesions after transsphenoidal surgery is the best alternative in cases of active bleeding.